COMPLICATIONS OF CATARACT SURGERY IN PATIENTS WITH PSEUDOEXFOLIATION SYNDROME - Jawad, Mohammad; Nadeem, Aqil -ur-Rehman; Khan, Aleem ul Haq; Aftab, Mohammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: The weak zonule’s predisposition to complications during conventional cataract surgery is one of the common risk factor for poor visual acuity after surgery. The present study was conducted to determine the frequency and types of complications during cataract surgery in patients with Pseudoexfoliation Syndrome. Methods: A cross sectional descriptive study based on non probability sampling of patients having pseudoexfoliation syndrome admitted for cataract surgery in tertiary care hospitals was carried out spread over 4 years. The data of all variables of interest were entered and analyzed through SPSS version 15.0. Results: A total of 200 eyes of 122 patients having Psuedoexfoliation were included in the study. Vitreal prolapse in 21 (10.5%) and posterior capsular rupture in 18 (9%) patients were the most common complications seen in Pseudoexfoliation. Damage to sphincter pupillae in 16 (8%), iridodialysis in 2 (1%), decentration of IOL in 8 (4%) and hyphaema in 2 (1%) patients was seen. Zonular dialysis in 8 (4%), retained lens matter in 12 (6%) and lens dislocation was seen in 6 (3%) patients. Conclusion: Patients with pseudoexfoliation are at increased risk for development of complications. Ophthalmologists should stress to increase awareness among general public for the proper diagnosis and convince patients for proper and regular follow up visits to the hospital. Keywords: Pseudoexfoliation, Cataract, Complications, Intraocular pressure